VoLTE Implementation with Software Open5GS, SrsRAN, and Kamailio Using SDR with a Billing System - Marantika, Andry Septian; Muhammad Syirajuddin Suja'I; Ahmad Wilda Yulianto (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2026)
In the initial implementation of LTE networks, voice calls still required a fallback to GSM or 2G (Circuit-Switched Fallback), resulting in service interruptions and the inability to maintain simultaneous data sessions. This study proposes an open-source-based implementation of Voice over LTE (VoLTE) by integrating Kamailio as the IP Multimedia Subsystem (IMS), Open5GS as the Evolved Packet Core (EPC), and srsRAN as the eNodeB. The system was designed and tested to provide native voice services over LTE without disrupting internet connectivity. The test results show that the proposed architecture successfully enables simultaneous voice calls and internet access without network fallback to GSM/3G. Signal quality measurements recorded a Reference Signal Received Power (RSRP) of -83 dBm for UE-1 and -82 dBm for UE-2, Reference Signal Received Quality (RSRQ) of -9 dB for both, and a Signal-to-Noise Ratio (SNR) of 13 dB. FTP throughput tests achieved download speeds of up to 404.88 KB/s and upload speeds of 105.98 KB/s during active calls. Latency averaged 32 ms, jitter was 4 ms, and packet loss was 0.96% for UE-1 and 0.97% for UE-2, all within the standard VoLTE quality thresholds. In addition, the system supports IMS-based SMS services and multi-eNodeB operations, including handover processes without call drops. These findings demonstrate that the developed LTE SDR-based VoLTE network can deliver high-quality, stable, and fully packet-based voice communication services, meeting or exceeding recommended technical performance